2016
DOI: 10.1093/toxsci/kfw096
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Doxorubicin Toxicity in Pancreatic β-Cells

Abstract: Exposure to chemotherapeutic agents has been linked to an increased risk of type 2 diabetes (T2D), a disease characterized by both the peripheral insulin resistance and impaired glucose-stimulated insulin secretion (GSIS) from pancreatic β-cells. Using the rat β-cell line INS-1 832/13 and isolated mouse pancreatic islets, we investigated the effect of the chemotherapeutic drug doxorubicin (Adriamycin) on pancreatic β-cell survival and function. Exposure of INS-1 832/13 cells to doxorubicin caused impairment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
0
9
0
2
Order By: Relevance
“…Doxorubicin administration is an effective treatment for several types of cancer and primarily functions through the promotion of cellular apoptosis ( Rochette et al, 2015 ). However, this therapy has highly undesired side effects including, but not limited to, widely reported cardiotoxicity ( Benjamin et al, 1974 ), DX also disrupts glucose and lipid metabolism and affects whole-body homeostasis ( Biondo et al, 2016 ; De Lima Junior et al, 2016 ; Heart et al, 2016 ). We demonstrated that doxorubicin treatment caused a reduction in glucose uptake after insulin stimulation and caused marked fibrosis in SAT.…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin administration is an effective treatment for several types of cancer and primarily functions through the promotion of cellular apoptosis ( Rochette et al, 2015 ). However, this therapy has highly undesired side effects including, but not limited to, widely reported cardiotoxicity ( Benjamin et al, 1974 ), DX also disrupts glucose and lipid metabolism and affects whole-body homeostasis ( Biondo et al, 2016 ; De Lima Junior et al, 2016 ; Heart et al, 2016 ). We demonstrated that doxorubicin treatment caused a reduction in glucose uptake after insulin stimulation and caused marked fibrosis in SAT.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent in vivo and in vitro studies observed decreased SIRT1 (Wang et al 2017;Zhu et al 2017) and SIRT3 (Cheung et al 2015;Pillai et al 2016) mRNA-expression and protein levels after DOX administration. Additionally, the metabolic shifts resultant from cardiac-DOX exposure have also shown to alter mitochondrial pathways for ATP production that could ultimately result in dysregulated NAD + /NADH ratios and NAD + levels, important linkers with the circadian regulation (Heart et al 2016;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism can be enhanced by redox cycling and production of H 2 O 2 . 51 The results are presented in Fig. 7.…”
Section: Cell Viability Assays and Uptake Studiesmentioning
confidence: 99%